2013
DOI: 10.3892/or.2013.2293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plant extracts sensitizing breast cancer cells to TRAIL

Abstract: Abstract. Triple-negative breast cancer (TNBC) is an aggressive heterogeneous cancer subgroup with a higher rate of distant recurrence and a poorer prognosis compared to other subgroups. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is an attractive molecule that induces cell death in various tumor cells without causing cytotoxicity to normal cells; however, primary or acquired resistance to TRAIL often limits its efficacy in cancer patients. To develop combination therapies to improve TRAIL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…TRAIL is a member of the TNF super family that can initiate apoptosis by activation of death receptor 4 (DR4/ TRAILR-1) and death receptor 5 (DR5/TRAILR-2). Since TRAIL can induce apoptosis in cancer cells, including breast cancer cells, without causing toxicity to normal cells (Chinnaiyan et al, 2000;Keane et al, 1999;Walczak et al, 1999), strategies which target TRAIL represent safe alternatives for cancer therapy development (Abdelhamed et al, 2013).…”
Section: Dandelion Extracts Inhibited the Breast Cancer Stem Cell Promentioning
confidence: 99%
“…TRAIL is a member of the TNF super family that can initiate apoptosis by activation of death receptor 4 (DR4/ TRAILR-1) and death receptor 5 (DR5/TRAILR-2). Since TRAIL can induce apoptosis in cancer cells, including breast cancer cells, without causing toxicity to normal cells (Chinnaiyan et al, 2000;Keane et al, 1999;Walczak et al, 1999), strategies which target TRAIL represent safe alternatives for cancer therapy development (Abdelhamed et al, 2013).…”
Section: Dandelion Extracts Inhibited the Breast Cancer Stem Cell Promentioning
confidence: 99%
“…They are a group of bacteria, reported to produce great variety of bioactive secondary metabolites and represent a focal point in the search for novel antimicrobials and anticancer agents (36,37). The cytotoxic effect of several plant and marine sponge extracts against various tumor cell lines was reported (38)(39)(40)(41)(42)(43). However, the anticancer effect of crude extracts isolated from marine microorganisms has not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts as a traditional remedies are already being used to treat a variety of diseases including cancer (Zheng et al, 1992;Svejda et al, 2010;Khan et al, 2011;Randhawa and Alghamdi, 2011;Sharma et al, 2011). The utilization of medicinal plants is more common in underdeveloped countries (Heck et al, 2000) and experimental studies showed that the extracts of the various plants can also protect against breast cancer cells (Pratumvinit et al, 2009;Abu-Dahab et al, 2012;Abdelhamed et al, 2013). In the view to the above mentioned facts, the present study was designed to evaluate the potential therapeutic capabilities of anticancer property of alcoholic extract and oil of Petroselinum sativum (P. sativum) seeds in MCF-7 cells, a human breast adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since many years, plant Nida Nayyar Farshori 1 *, Ebtesam Saad Al-Sheddi 1 , Mai Mohammad Al-Oqail 1 , Javed Musarrat 2 , Abdulaziz Ali Al-Khedhairy 2 , Maqsood Ahmed Siddiqui 2 extracts have been used as traditional remedies to treat a various diseases including cancer (Salem, 2005;Padhye et al, 2008;Gaidhani et al, 2009;Svejda et al, 2010;Khan et al, 2011;Randhawa and Alghamdi, 2011;Sharma et al, 2011). Experimental studies also revealed that seed oil and extracts of the various plants can also protect against human breast cancer (Pratumvinit et al, 2009;Abu-Dahab et al, 2012;Abdelhamed et al, 2013). The Petroselinum sativum (P. sativum) or parsley, a member of the family of Umbelliferae, has been reported to have antioxidant (Kreydiyyeh et al, 2001;Ahmed et al, 2010), antidiabetic (Yanardag et al, 2003), antiinflammatory, antiedema antihypertensive, antimicrobial (Wahba et al, 2010) activities.…”
Section: Introductionmentioning
confidence: 99%